2017
DOI: 10.1177/0033688216684279
|View full text |Cite
|
Sign up to set email alerts
|

Improving Readability in an Explicit Genre-based Approach: The Case of an EFL Workplace Context

Abstract: The present study investigates how learners of English as a foreign language (EFL) improve the readability of their texts in an explicit genre-based approach that is utilized in an oil and gas exploration workplace in Angola. By drawing on the English for Specific Purposes and Systemic Functional Linguistics genre traditions, the study engages 18 intermediate learners (14 males and 4 females) in an explicit instruction of an email making a request and assesses how learners’ written products improve in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Studies on genre-based pedagogy have shown the innovations of the GBT cycles for improving English language students' knowledge of genre as TLCs of GBT (e.g., Albino, 2017;Emilia & Hamied, 2015;Huang & Zhang, 2019;Widodo, 2006;Yasuda, 2011). Such eclectic modifications by blending the strengths of relevant methods or procedure were made to cater instructional as well as curricula purposes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on genre-based pedagogy have shown the innovations of the GBT cycles for improving English language students' knowledge of genre as TLCs of GBT (e.g., Albino, 2017;Emilia & Hamied, 2015;Huang & Zhang, 2019;Widodo, 2006;Yasuda, 2011). Such eclectic modifications by blending the strengths of relevant methods or procedure were made to cater instructional as well as curricula purposes.…”
Section: Introductionmentioning
confidence: 99%
“…This condition, therefore, suggests the provision of a GBT model for guiding teachers to properly enact GBT practices within the GBT methodology. Although the aforementioned studies on GBT (e.g., Albino, 2017;Emilia & Hamied, 2015;Huang & Zhang, 2019;Widodo, 2006;Yasuda, 2011) have made particular eclectic modifications of the GBT cycle to accommodate instructional and curricula purposes, little is known about the modification of the GBT cycle for accommodating varied curriculum contents, as the 2013 Indonesian EFL curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…The innovation of genre-based tasks, for example, emerges in response to students' learning needs in learning specific content (English for Specific Purposes or ESP) (Albino, 2017). Through ESP, students learn how to construct real-life genres (Yasuda, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Through ESP, students learn how to construct real-life genres (Yasuda, 2011). In addition to implementing the teaching and learning cycle, such an approach uses a particular stage called a situated practice for engaging students in multifaceted literacy practices (Ranker, 2009), and applies genrebased tasks, which combine genre-based and task-based instruction (Albino, 2017;Yasuda, 2011). Genre-based pedagogy has been widely adopted in instruction and is widely researched in many parts of the world including Southeast Asian countries such as Indonesia, Singapore, Vietnam, Hongkong, and Japan; European countries such as Germany, France, Denmark, Sweden; and South American countries such as Brazil and Argentina (Emilia, Christie, & Humphrey, 2012cited in Emilia & Hamied, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…A study on text readability found that the genre-based approach improves the readability of EFL students' texts. Explicit genre instruction improved the structure and linguistics choices (Albino, 2017). Research also reported that genre-based teaching facilitates the students to write successfully.…”
Section: Introductionmentioning
confidence: 88%